Private Sector Initiatives to Boost Productivity of Cocoa, Coffee, and Rubber in Indonesia - Mercyta Jorsvinna Glorya; Arief Nugraha (Center for Indonesian Policy Studies (CIPS), 2019)
Indonesian farmers growing cocoa, coffee and rubber are struggling to maintain productivity levels needed to supply demand. Farmers face tough challenges to provide the quality and quantity buyers need, and face stiff competition from farmers in other countries. As a result, many farmers turn away from these commodities in search of more promising sources of livelihoods. Government programs have been created to incentivise and improve availability of resources farmers need to grow these commodities, yet, in our latest paper, we discuss how private sector actors have been the most effective in supporting farmers.
Keywords: 330